La transformation des Landes de Gascogne (xviiie-xixe), de la mise en valeur comme colonisation intérieure ? - Julien Aldhuy (Confins)
When one evokes the development of the Moors of Gascony, one thinks of the transformation of this area at the 19th century by a forestation with maritime pines thanks to a systematic drainage. This simplification inherited of the history of the French Nation-State raises two problems. Firstly, it reduces the transformation of the Moors of Gascony to a decontextualized local history, without links with the ideas and the stakes of the time. Secondly, such a reduction supports a dissocialized reading of the production of this space because one only retains the means of the action (the drainage) and its result (the forest of pine). Such a posture implies a vision devoid of actors and of relationship of domination between those which disqualify space and justify the compensation action and those which live in. We will show in this article that once put in context in the concert of the ideas of the time and once the place of its actors restored, the development of the Moors of Gascony can be considered like an interior colonization.